Effect of three months of soft contact lens wear on conjunctival cytology - Sapkota, Kishor (2016)
Background: The purpose of this study was to investigate the effect of three months of soft contact lens wear on conjunctival goblet cell density and epithelial cell morphology. Methods: This was a longitudinal clinical trial. Conjunctival impression cytology was performed on the superior palpebral conjunctiva in fifty-four eyes of twenty-seven neophyte contact lens wearers before and after three months of contact lens wear. Goblet cell density was determined by optical microscopy and epithelial cell morphology was classified according to the Tseng classification. Changes in goblet cell density as well as epithelial cell grading were determined. The effects of lens material and wearing modality on cytological changes were also investigated. Results: Goblet cell density reduced significantly by 85 ± 151 cells/mm2 (p<0.001) after three months of contact lens wear. Reduction in goblet cell density was associated with lensmaterials; it was higher in conventional hydrogel lenses in comparison to silicone-hydrogel lenses (p = 0.008). The highest reduction in goblet cell density was found with Nelfilcon A lens wear (p = 0.002) and the lowest with Comfilcon A lens wear (p = 0.414). There was no statistically significant difference in grading of epithelial metaplasia before and after three months of contact lens wear (p = 0.075). Age was not correlated with the reduction in goblet cell density (r = -0.196, p = 0.160) but it was associated with the change in epithelial cell morphology (p = 0.036). Conclusion: Three months of soft contact lens wear statistically significantly reduced goblet cell density; however, no significant changes were found in the grading of epithelial metaplasia. Contact lenses with lower oxygen permeability, higher Young modulus and higher thickness highly affected the conjunctival cytology.